RETRACTED: New algorithms for numerically solving a class of bordered tridiagonal systems of linear equations. (1st July 2019) - Jia, Jiteng; Li, Sumei
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editors-in-Chief. After a thorough investigation, the Editors have concluded that the acceptance of this article was based upon the positive advice of at least one illegitimate reviewer report. The report was submitted from an email account which was provided to the journal as a suggested reviewer during the submission of the article. Although purportedly a real reviewer account, the Editors have concluded that this was not of an appropriate, independent reviewer. This manipulation of the peer-review process represents a clear violation of the fundamentals of peer review, our publishing policies, and publishing ethics standards. Apologies are offered to the reviewers whose identities were assumed and to the readers of the journal that this deception was not detected during the submission process.